Dispersive solid-phase microextraction with graphene oxide based molecularly imprinted polymers for determining bis(2-ethylhexyl) phthalate in environmental water - Cheng, Lidong; Pan, Shuihong; Ding, Chuyuan; He, Jun; Wang, Chengjun (Elsevier, 2017)
A novel graphene oxide-molecularly imprinted polymers (GO-MIPs) was prepared and applied for selective extraction and preconcentration of bis(2-ethylhexyl) phthalate (DEHP) in environmental water samples by using the dispersive solid-phase microextraction (DSPME) method. The GO-MIPs was synthesized via precipitation polymerization using GO, DEHP, methacrylic acid, and ethylene dimethacrylate as supporting materials, template molecules, functional monomer, and cross-linker, respectively. The prepared GO-MIPs were characterized by scanning electron microscope and Fourier transform infrared spectroscopy. The GO-MIPs-DSPME conditions including type and volume of elution solvents, adsorbents amount, initial concentration of DEHP, pH and ionic strength of water samples were investigated. Under optimized conditions, the DEHP was selectively and effectively extracted in real water samples and enrichment factors of over 100-fold were achieved. Good linearity was obtained with correlation coefficients (R2) over 0.999 and the detection limit (S/N = 3) was 0.92 ng mL−1. The average recoveries of the spiked samples at three concentration levels of DEHP ranged from 82% to 92% with the relative standard deviations less than 6.7%. The results indicated that the proposed GO-MIPs-DSPME extraction protocol combined with HPLC-UV determination could be applied for selective and sensitive analysis of trace DEHP phthalate in environmental water samples.